1990
DOI: 10.1192/bjp.157.2.261
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Psychological and Social Change after Surgical Gender Reassignment in Selected Male Transsexuals

Abstract: Of two groups of 20 patients accepted for gender reassignment surgery, one was offered early operation and therefore had had surgery by follow-up two years later, while the second was still awaiting operation at two-year follow-up. Although the groups were similar initially, significant differences between them emerged at follow-up in terms of neuroticism and social and sexual activity, with benefits being enjoyed by the operated group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 15 publications
1
33
0
2
Order By: Relevance
“…High percentages of psychiatric comorbidity, however, are not always found. In many studies, transsexuals were found to generally function well psychologically in the nonclinical range (e.g., Cole, O'Boyle, Emory, & Meyer, 1997;Gómez-Gil, Trilla, Salamero, Godás, & Valdés, 2009;Haraldsen & Dahl, 2000;Mate-Kole, Freschi, & Robin, 1990;Miach, Berah, Butcher, & Rouse, 2000;Seikowski, Gollek, Harth, & Reinhardt, 2008;Smith, van Goozen, & CohenKettenis, 2001;Smith et al, 2005). Indeed, clinically, one may see applicants who are employed, have relationships, and function socially without any problems, yet very strongly desire sex reassignment.…”
Section: The Necessity Of the D Criterion For A Gid Diagnosismentioning
confidence: 99%
“…High percentages of psychiatric comorbidity, however, are not always found. In many studies, transsexuals were found to generally function well psychologically in the nonclinical range (e.g., Cole, O'Boyle, Emory, & Meyer, 1997;Gómez-Gil, Trilla, Salamero, Godás, & Valdés, 2009;Haraldsen & Dahl, 2000;Mate-Kole, Freschi, & Robin, 1990;Miach, Berah, Butcher, & Rouse, 2000;Seikowski, Gollek, Harth, & Reinhardt, 2008;Smith, van Goozen, & CohenKettenis, 2001;Smith et al, 2005). Indeed, clinically, one may see applicants who are employed, have relationships, and function socially without any problems, yet very strongly desire sex reassignment.…”
Section: The Necessity Of the D Criterion For A Gid Diagnosismentioning
confidence: 99%
“…The lengthy process is often cited as a contributory factor in the development of comorbid psychiatric problems, and untreated gender dysphoria can be associated with significant psychological distress and is a risk factor for suicide. 2 The costs of treatment need to be weighed up against the ongoing costs of supporting the mental healthcare needs of those awaiting genital surgery.…”
Section: Original Papersmentioning
confidence: 99%
“…1 The outcome of premorbid psychopathology following gender reassignment surgery is unclear. Mate-Kole et al 2 reported improvements in sexual functioning and neurotic symptoms, whereas Udeze et al 4 reported no significant effect on psychological functioning 6 months post-surgery. Following a successful appeal against a local health authority in 1999, 5 a blanket ban on funding of medical treatment for gender reassignment was deemed illegal and those diagnosed with gender identity disorder are entitled to appropriate treatment in the National Health Service (NHS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patient satisfaction following SRS is high [3,4] and the reduction of gender dysphoria following SRS results in considerable psychological and social benefits [5,6]. As with all surgical interventions, the quality of care provided before, during, and after SRS has an important impact on patient outcomes [7].…”
Section: Introductionmentioning
confidence: 99%